The Family Law Bar, the Interdisciplinary Resource Center for Separating and Divorcing Parents, and the "Spark to Kindle the White Flame of Progress". (January 2017) - Schepard, Andrew; Kline Pruett, Marsha; Kourlis, Rebecca Love
Abstract : The Interdisciplinary Resource Center for Separating and Divorcing Families at the University of Denver described in the Honoring Families Initiative's Family Law Bar Report provides a suite of holistic services tailored to the individual needs of families with children. Services provided include assessment and service planning, legal education, dispute resolution (mediation), agreement and order drafting, therapeutic services, and financial planning. As established by a rigorous empirical evaluation, parents and children appreciate and benefit from these coordinated, holistic services. The Center experience gives evidence of the value of interdisciplinary collaboration. It is our hope that the Family Law Bar will be inspired to promote the development of Centers throughout the country and promote changes in legal regulation and education to facilitate interdisciplinary collaborations for the benefit of separating and divorcing families. Key Points for the Family Court Community: The Resource Center experience establishes that holistic problem‐solving‐focused services provided by interdisciplinary teams that include lawyers benefit separating and divorcing parents and children. The traditional model of delivering legal services to parents in separation and divorce requires each to be represented by his/her own lawyer. That model is not economically viable for many families. Center parents, in contrast, receive legal information from a single source—Center mediators and legal educators. The positive impact of Center services suggests that the traditional model is not optimal in many cases and regulatory changes should be made to give parents an option to use just one lawyer, with informed consent. The Family Law Bar can use the Center experience as inspiration to collaborate with other professions to develop innovative multidisciplinary service delivery models for parents and children in separating and divorcing families and to re-examine regulatory barriers to interdisciplinary collaboration.